Efecto de la densidad de siembra en el crecimiento de juveniles de Paiche (Arapaima Gigas) en estanques de la Estación Pesquera Ahuashiyacu - Fernández Barrera, Bertha Almeyra (2010)
This study had as purpose evaluate the influence of sowing density in the growth of juvenile of paiche Arapaima gigas (cuvir, 1829) in controlled environments of the Ahuashiyacu Fishing Station. We worked with 10 ponds of 300m2 located on the line “B” on the Ahuashiyacu Fishing Station and with a depth of 1, 5 m. A design was applied completely at random by three treatments and a witness group of comparison (T1:1pez/11m2, T2:1pez/16m2, T3: 1pez/21m2) and a witness group 1pez/ 9m2 with three repetitions; 210 paiches were sowed with a length and average weight of 75,4 cm and 3,7 kg respectively. Biometric evaluations were performed monthly, obtaining samples over 20% for experimental unit, reporting information at the end of the experiments length and average weight of 8, 3 kg and 93.4 cm. At 180 days of rearing, the results indicate that have existed significant differences between treatments, being 03rd treatment of 1pez/ 21m2 which gave better results compared with 1st treatment of 1pez/ 11m2 which gave lower results.